Guide to construction and use of 90 mm (3.5 in) flexible disk cartridges for data interchange, using modified frequency modulationrecording at 7958 ftprad, 5.3 tpmm (135 tpi) on 80 tracks on each side. Track format Part 2, (30th September 1988) - British Standards Institution,
No abstract available